Stem anatomy and development of successive cambia in Hebanthe eriantha (Poir.) Pedersen: A neotropical climbing species of the Amaranthaceae - Rajput, Kishore Shankersinh [UNESP]; Marcati, Carmen Regina [UNESP] (Springer Nature, 2013)
Hebanthe eriantha (Poir.) Pedersen, a climbing species of the Amaranthaceae increases in stem thickness by forming successive cambia. The family is dominated by herbaceous species and is constantly under discussion due to its disputed nature of the meristem. In the young stem small alternate segments of vascular cambium cease to divide and new arc of cambium initiates outside to it. The newly formed arcs connect with pre-existing alternate segments of cambium to complete the ring. On the contrary, in thick stems, instead of small segments, complete ring of cambium is replaced by new one. These new alternate segments/cambia originate from the parenchyma cells located outside to the phloem produced by previous cambium. Cambium is storied and exclusively composed of fusiform initials while ray cells remain absent at least in the early part of the secondary growth. However, large heterocellular rays are observed in 15-mm diameter stems but their frequency is much lower. In some of the rays, ray cells become meristematic and differentiate into radially arranged xylem and phloem elements. In fully grown plants, stems are composed of several successive rings of secondary xylem alternating with secondary phloem. Secondary xylem is diffuse-porous and composed of vessels, fibres, axial parenchyma while exceptionally large rays are observed only in the outermost regions of thick stems. Vessel diameter increases progressively from the centre towards the periphery of stems. Although the origin of successive cambia and composition of secondary xylem of H. eriantha remains similar to other herbaceous members of Amaranthaceae, the occurrence of relatively wider and thick-walled vessels and large rays in fully grown plants is characteristic to climbing habit. © 2013 Springer-Verlag Wien.
Keywords: Amaranthaceae; Anomalous secondary growth; Cambial variant; Climbing habit; Hebanthe; Secondary growth; Successive cambia